The female philosopher and her afterlives : Mary Wollstonecraft, the British novel, and the transformations of feminism, 1796-1811 /: Mary Wollstonecraft, the British novel, and the transformations of feminism, 1796-1811. (2017) - Weiss, Deborah
No abstract available